2013
DOI: 10.1029/2012jd017501
|View full text |Cite
|
Sign up to set email alerts
|

Global transients in ultraviolet and red‐infrared ranges from data of Universitetsky‐Tatiana‐2 satellite

Abstract: [1] Light detectors sensitive to wavelength ranges 240-400 nm and beyond 610 nm (which we refer to, for simplicity, as the UV and Red bands) on board UniversitetskyTatiana-2 satellite have detected transient flashes in the atmosphere of duration 1-128 ms. Measured ratio of the number of Red photons to the number of UV photons indicates that source of transient radiation is at high atmosphere altitude (>50 km). Distribution of events with various photon numbers Q a in the atmosphere found to be different for "l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 19 publications
2
44
0
7
Order By: Relevance
“…Analysis of correlation between clouds and any TAE (in series or not) is also in contradiction to the lightning origin of some TAE. An equal numbers of transients in both cloudy and cloudless areas of the atmosphere (Vedenkin et al 2011;Garipov et al 2013) were observed, while lightning was strongly correlated to clouds. Those data will be confirmed by new measurements with better identification of TAE and lightning.…”
Section: Scientific Background Phenomenology Of Transient Atmospherimentioning
confidence: 94%
See 4 more Smart Citations
“…Analysis of correlation between clouds and any TAE (in series or not) is also in contradiction to the lightning origin of some TAE. An equal numbers of transients in both cloudy and cloudless areas of the atmosphere (Vedenkin et al 2011;Garipov et al 2013) were observed, while lightning was strongly correlated to clouds. Those data will be confirmed by new measurements with better identification of TAE and lightning.…”
Section: Scientific Background Phenomenology Of Transient Atmospherimentioning
confidence: 94%
“…One can see that short transients are numerous and have fewer UV photons than longer ones. It was also shown in Garipov et al (2013) that short TAE are not concentrated to equatorial latitudes as longer ones. Whether this is a triggering effect or a physical phenomenon will be clarified during measurements onboard the Lomonosov satellite.…”
Section: Scientific Background Phenomenology Of Transient Atmospherimentioning
confidence: 94%
See 3 more Smart Citations